[Hills Surrounding Lake Viti] - Streng, Evelyn Fiedler (1975)
Photograph of the hills surrounding Lake Viti. The brown, rocky hills stand tall along the background of the photograph, its niches filled with now and grey dirt. A dark path cuts through the connecting point of two hills ahead, a group of people stood at the top of it. The edge of the grey lake is visible along the bottom edge of the photograph.